Pengaruh Kepemimpinan Transformasional Terhadap Motivasi dan Kinerja Guru yang Dimoderasi oleh Iklim Sekolah di MTsN 1 Medan - Muliati, Agustina (Islamic Education, 2022)
This research aims to examine the influence of transformational leadership and work motivation on teacher performance at MTsN 1 Medan moderated by school climate. The specific objectives are to test the effects of transformational leadership and work motivation on teacher performance moderated by the role of climate. The significance of this study lies in explaining and expanding on previous research regarding the impact of transformational leadership and work motivation on teacher performance moderated by school climate. The study involved 121 teachers from MTsN 1 Medan. Nonprobability sampling using purposive sampling method was employed. Based on the research findings, it can be concluded that transformational leadership significantly affects teacher performance, motivation does not affect teacher performance, school climate influences teacher performance, the impact of transformational leadership on teacher performance is moderated by school climate, and the impact of work motivation on teacher performance is not moderated by school climate.